Profitability of Technical Trading Rules in an Emerging Market - Dimitris Kenourgios; Spyros Papathanasiou (The Handbook of Trading: Strategies for Navigating and Profiting from Currency, Bond, and Stock Markets, 2010)
This chapter investigates the profitability of technical trading rules in the Athens Stock Exchange (ASE), utilizing the FTSE/ASE 20 index during the period 1995 to 2008. We focus on a less developed and efficient stock market, given the existing scarcity of research in such markets. The technical rules that will be explored are simple moving averages. We compare technical trading strategies in the spirit of Brock, Lakonishok, and LeBaron (1992), employing traditional t test and bootstrap methodology under the generalized autoregressive conditional heteroscedasticity model. The results provide strong evidence on the profitability of the technical trading rules against the “buy and hold” strategy and contradict the efficient market hypothesis.